Capacity utilization and admission control in the downlink of mobile wimax - Shu'aibu, Dahiru Sani (Praise Worthy Prize, 2010)
WiMAX is a broadband wireless technology that uses base station like the present GSM. WiMAX offers services to different traffic classes with different quality of services requirements. Unlike GSM, five different traffics were identified in WiMAX in which all subscribers can be in any of the traffics. These traffics are either constant bit rate application or variable bit rate. In this paper, we present a call admission control that divides the total bandwidth capacity (bit rate) of the down link in to constant bit rate traffics and variable bit rate traffics within the base station coverage and those out of coverage area through the relay station. The relay station is assumed to decode and forward. Eight different traffics were randomly deployed a number of times, in to the sector of the cell of the base station and the relay station. The traffics were admitted based on their signal to noise ratio (SNR), bit rate and availability of the bandwidth on the down link sub-frame. The results showed that the propose admission policy utilizes the capacity more efficiently and the bandwidth is well managed compare to the conventional policy in WiMAX system.